Efeito de um novo inibidor dos canais Co-Transportadores Sódio/Glicose (SGLT2) na homeostasia da glicose em diferentes modelos experimentais - Pereira, Landerson Lopes (2023)
Introduction: The Ministry of Health identifies Brazil as the 5th country with the highest incidence of diabetes in the world. The existing treatments for the disease have various limitations. SGLT2 inhibitors emerge with an insulin-independent mechanism of action, but the treatment is limited due to a slight to moderate increase in the incidence of genitourinary infections, among other minor complications. Thus, the importance of investigating new molecules arises, in order to refine treatment further. Objective: The present study aimed to determine the activity of a chemically synthesized compound, LASSBio-1986, an inhibitor of the SGLT2 sodium-glucose channels, in silico, in the regulation of glucose metabolism and in insulin-resistant animals. Methodology: The in silico analysis was conducted using specialized software, where predictive pharmacokinetics, toxicology, and pharmacodynamics were evaluated based on SwissADME, ProTox-II, DockThor, and ClusPro, respectively. Experiments in C57BL/6 strain mice evaluated the effect of LASSBio-1986 on blood glucose regulation, glycogen levels, oxidative stress, cytokine levels, insulin resistance, and GLUT-4 gene expression. Results: In an in silico model, the LASSBio-1986 compound showed good pharmacokinetics, with a balance between hydro and lipophilicity being adequate, in addition to the impossibility of permeating the blood-brain barrier. Regarding toxicology, the compound has a high level of safety, however with the possibility of mutagenic and immunotoxic action, requiring chronic in vivo tests to verify such data. In the GTT, the dose of 3mg/kg via i.p. notably reduced glucose levels after 15, 30, and 60 minutes in the glucose tolerance test. LASSBio-1986 3 mg/kg increased the level of glycogen in the liver and muscle and elevated glutathione levels in the liver, muscle, and kidneys. There was a reduction in reactive acid substances in the liver and kidney. The compound reduced the levels of pro-inflammatory cytokines in muscle, hepatic, and renal tissues. Furthermore, LASSBio-1986 3 mg/kg proved to be effective in increasing insulin sensitivity. LASSBio-1986 has remarkable action in regulating blood glucose and insulin resistance, in addition to reversing and increasing mRNA levels of GLUT-4.